6 - We Are the Sons of Mau Mau! Re-Assessing the Historiography of Resistance in Kenya, 1924-2008 - Mwangi J. Macharia (Afrika Zamani, 2022)
Mungiki is a politico-religious group and a banned criminal organization in Kenya. The organisation, which apparently originated in the late 1980s, is secretive and bears some similarity to mystery religions. Specifics of their origin and doctrines are unclear. What is clear is that they favour a return to indigenous African traditions and reject Westernisation and all trappings of colonialism. These include; rejection of Christianity, and the practice by the Mungiki of forced female genital cutting. The ideology of the group is characterised by revolutionary rhetoric, Kikuyu traditions, and a disdain for modernization, which is seen as immoral corruption. Their participation in recent ethnic wars in Kenya has evoked serious academic concerns on the group. What is interesting is that the followers of the so-called Mungiki youth sect, whose 500,000 members see themselves as ‘the true sons of the Mau Mau’. By using interdisciplinary approaches, I intend to show the myriad ways in which youth construct their own identity and how they derive power and inspirations from the past (Mau Mau). I not only introduce problems surrounding conceptions of Mungiki and the generation, but also show how conflicts between the young (Mungiki) and older (Mau Mau) generations reconfigure power in society.